Molecular Characterisation of Endophytic Fungi from Roots of Wild Banana (Musa acuminata) - Latiffah Zakaria,; Muhamad Izham Muhamad Jamil,; Intan Sakinah Mohd Anuar, (Tropical Life Sciences Research, 2016)
Endophytic fungi inhabit apparently healthy plant tissues and are prevalent in terrestrial plants, especially root tissues, which harbour a wide assemblage of fungal endophytes. Therefore, this study focused on the isolation and characterisation of endophytic fungi from the roots of wild banana (Musa acuminata). A total of 31 isolates of endophytic fungi were isolated from 80 root fragments. The endophytic fungi were initially sorted according to morphological characteristics and identified using the sequences of the translation elongation factor-1? (TEF-1?) gene of Fusarium spp. and the Internal Transcribed Spacer (ITS) regions of other fungi. The most common fungal isolates were species of the genus Fusarium, which were identified as F. proliferatum, Fusarium sp., F. solani species complex, and F. oxysporum. Other isolated endophytic fungi included Curvularia lunata, Trichoderma atroviride, Calonectria gracilis, Rhizoctonia solani, Bionectria ochroleuca, and Stromatoneurospora phoenix (Xylariceae). Several of the fungal genera, such as Fusarium, Trichoderma, Rhizoctonia, and Xylariceae, are among the common fungal endophytes reported in plants. This study showed that the roots of wild banana harbour a diverse group of endophytic fungi. Kulat endofitik mendiami tisu tumbuhan yang kelihatan sihat dan tersebar luas dalam tumbuhan daratan terutamanya tisu akar yang mengandungi himpunan pelbagai kulat endofitik. Kajian ini memberi tumpuan kepada pemencilan dan pencirian kulat endofitik yang terdapat dalam akar pisang liar (Musa acuminata). Sejumlah 31 pencilan kulat endofitik telah dipencilkan daripada 80 fragmen akar. Kulat endofitik tersebut pada mulanya diasing berdasarkan ciri-ciri morfologi dan dikenal pasti menggunakan jujukan gen faktor pemanjangan translasi-1? (TEF-1?) untuk mengenalpasti Fusarium spp. dan kawasan Internal Transcribed Spacer (ITS) digunakan untuk kulat yang lain. Spesies kulat yang paling lazim dipencilkan adalah Fusarium dan pencilan-pencilan tersebut telah dikenal pasti sebagai F. proliferatum, Fusarium sp., kompleks spesies F. solani dan F. oxysporum. Kulat endofitik lain yang telah dipencilkan adalah Curvularia lunata, Trichoderma atroviride, Calonectria gracilis, Rhizoctonia solani, Bionectria ochroleuca, dan Stromatoneurospora phoenix (Xylariceae). Beberapa genus kulat seperti Fusarium, Trichoderma, Rhizoctonia, dan Xylariceae merupakan antara kulat endofitik lazim yang dilaporkan dalam tumbuhan. Kajian ini menunjukkan bahawa akar pisang liar mengandungi pelbagai kumpulan kulat endofitik.